Gratitude mediates the effects of power on prosociality - Wei Cai; Ying Yang (Social Influence)
Does gratitude mediate the relationship between power and prosociality? To answer this question, two studies were conducted to investigate the effects of social power on both reciprocal and non-reciprocal prosociality through gratitude. Study 1 (n = 193), utilizing a cross-sectional design, found that sense of power was positively associated with both reciprocal and non-reciprocal prosociality, with feelings of gratitude serving as a mediator in these associations. Study 2 (n = 199) manipulated power and demonstrated that holding power, as compared to lacking it, increased feelings of gratitude, which subsequently enhanced reciprocal prosociality. Through two studies, the current research addressed whether and why power influences prosocial behavior. The findings contribute to the theories of gratitude, power, and prosociality. Our study also sheds light on the practices within both positive and social psychology.